Group Offending in Mass Atrocities: Proposing a Group Violence Strategies Model for International Crimes - Rauxloh, Regina (Oñati Socio-Legal Series, 2016)
Most research in mass atrocities, especially genocide, is conducted at the macro level exploring how mass violence is instigated, planned and orchestrated at the level of the state. This paper on the other hand suggests that more research of the individual perpetrator is needed to complement the understanding of mass atrocities. The author develops therefore a new model, the group violence strategies model. This model combines various traditional criminological models of group offending and proposes a three stage analysis, looking at the individual aggressor, the actions within the offender group and the actions between offender group and victim group to understand better the phenomenon that ordinary people commit unspeakable crimes.